Lived Experiences of Workplace Bullying at the University of Education, Winneba, Ghana - Adrah, Rose (Ghana Journal of Higher Education Management, 2024)
Bullying was traditionally associated with the playground, but it is becoming a real menace in the workplace in the new millennium. It is usually a complex problemwhich requires a pragmatic solution. This is because bullying as behaviour is not always obvious. It can be irrational, subtle and devious, taking place when there areno witnesses, inflicted on colleagues and subordinates to cause maximum humiliation. Bullying takes place in almost all workplaces; UEW is no exception. This research paper brings to the fore, lived experiences on “bullying in the workplace” of fifty (50) members of staff. It ends with suggestions to administrators to help reduce this behaviour at UEW. The writer has the conviction that there is no place for bullies in any well-run organization such as our universities.